Skeletal metastases presenting as superscan on technetium 99m methylene diphosphonate whole body bone scintigraphy in different type of cancers: A 5-year retro-prospective study - P. Ram Manohar; Tanveer Rather; Shoukat Khan; Dharmender Malik (World Journal of Nuclear Medicine)
The purpose of the study is to find out the overall incidence of superscan among different type of cancers, causes of superscan and its relationship with other parameters such as age, sex, duration of disease, and serum alkaline phosphatase (ALP) levels. This was a retro-prospective study. Records of all previous bone scans and reported patients of superscan were re-evaluated retrospectively. Patients who were diagnosed as having superscan in the preceding 3 years with confirmed histopathological diagnosis were included in the retrospective group. In the prospective group, all the patients who were reported to have superscan appearance over the past 2 years of prospective period were included. Total of 6027 bone scans were examined in a 5-year period and out of which 80 cases were diagnosed as superscan. The overall incidence of superscan in different type of cancers was 1.3% (80/6027). Prostate cancer (46/80) was the most common cause of superscan appearance followed by breast cancer (10/80). Out of 6027 patients referred for bone scan, 307 patients had prostate cancer on histopathological examination. Out of 307 patients with prostate cancer, 46 had superscan appearance. Incidence of superscan in prostate cancer was 14.98% (46/307), and 71.73% (33/46) prostate cancer patients with superscan had Gleason score of 8 and above 8 with mean serum prostate-specific antigen level was 178.42 ng/ml in symptomatic patients and 122 ng/ml in asymptomatic patients. Out of all patients with superscan, 71 patients (88.7%) had elevated serum ALP levels. Overall incidence of superscan in our study was 1.3% in different type of cancer patients, and the most common cause of superscan appearance was prostate cancer. Incidence of superscan appearance in prostatic cancer patients was 14.98%.